Water dynamics of LiCl solutions confined in nanopores - Beckert, Steffen; Stallmach, Frank (Diffusion Fundamentals, 2013)
The self-diffusion of water in aqueous solutions of lithium chloride in bulk solutions and in these solutions confined to porous glass monoliths with bimodal pore structure has been studied by PFG NMR. The concentration dependent data for the bulk solutions are analyzed by the description of Sevrugin et al. [1], which yields information about the water dynamics within the ion’s hydration shell. For an application to confined diffusion, this description is extended by introducing a tortuosity factor. Whereas in the larger macropores no influence on the water dynamics within the hydration shell is detected, in the smaller mesopores, a significant increase of the mobility of the hydrating water molecules is observed.